การศึกษาลักษณะสัณฐานวิทยาของบัวบกสายพันธุ์ต่าง ๆ - พิริยะภัทรกิจ, อนันต์; รูปเลิศ, พรกมล; อัมพรายน์, กนกอร; จันจุฬา, ณัฐพงค์ (Thai Journal of Science and Technology, 2019)
Abstract Sixteen local pennywort plants distributed throughout Thailand were collected and grown in experimental plots at Expert Center of Innovative Agriculture, Thailand Institute of Scientific and Technological Research (TISTR), Khlong Ha, Khlong Luang, Pathum Thani. Morphological study of the 16 Asiatic pennyworts revealed that local Thai centella could be categorized into 2 groups, small leaf and big leaf. The small leaf group represented leaf diameter of 2.5-4.5 centimeters, while the big leaf group were more than 5.0 centimeters. Small leaf pennywort has been found to distribute in Loei, Kalasin, Burirum, Chiang Rai, Chiang Mai, Nan, Nonthaburi, Nakhonpathom, Samut Prakan, and Rayong Province, while the big leaf pennywort distributed in Ubon Ratchathani, Nongbua Lamphu, Khonkean, Prachinburi, and Nakhonsri Thammarat. Moreover, it was acknowledged that pennywort plants belonged to the big leaf group that exhibited longer leaf stalk, root, stolon, and flower stalk than those in the small leaf group. Additionally, there were some more differences between pennywort collected from different cities such as leaf margin, leaf color, and leaf stalk and stolon color. Thus, pennywort was able to categorize by these appearances into other 4 groups of shallow- and deep crenate, green leaf stalk & stolon, and green-brownish purple leaf stalk and reddish-purple stolon. The collected pennywort from Ubon Ratchathani, Khonkean, Nonbua Lamphu, Burirum, Chiang Rai, Chiang Mai, Nan, Nonthaburi, and Nakhonsri Thammarat presented green leaf stalk and stolon, whilst the pennywort from Loei, Kalasin, Nakhonpathom, Prachinburi, and Rayong exhibited green-brownish purple leaf stalk and reddish-purple stolon. Keywords: Centella asiatica; collection; morphology